TEACHING READING COMPREHENSION THROUGH SUMMARIZING TRAINING CAMP TECHNIQUE TO THE TENTH GRADE STUDENTS OF SMA NEGERI 5 LUBUKLINGGAU IN THE ACADEMIC YEAR OF 2015/2016 - Episiasi E.; Alen Syahputra (LP4MK STKIP PGRI Lubuklinggau, 2015)
The problem of the study was “Is it significant ly effect ive after the application of Summarizing Training Camp Technique on teaching reading comprehension to the tenth grade students of SMA Negeri 5 Lubuklinggau in the academic year of 2015/2016?”. The objective of this study was to find out whether or not there is significantly effective on reading comprehension after the application of Summarizing Training Camp Technique to the tenth grade students at SMA Negeri 5 Lubuklinggau. In this study, the writer proposed two hypotheses. They were null hypothesis (Ho) and alternative hypothesis (Ha). The method applied was pre-experimental with one group pre-test posttest design. The population of this study was all of the tenth grade students of SMA Negeri 5 Lubuklinggau which consisted of 245 students. The sample was taken through convenience random sampling which consisted of 40 students. The data were collected by means of test consisting 25 items of multiple choices. The data obtained were analyzed through three techniques: 1) Individual Score, 2) Conversion of Individual Score Based on Minimum Mastery Criteria, and 3) Matched t-test. The results of this study shows that the students’ mean score in the pre-test was 66.9 and those in the post-test was 76. The result of matched t test was 6.89, which was higher than t-table value (1.684) of 39 with 95% significant level for one tailed-test. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that it was significantly effective to use Summarizing Training Camp Technique in teaching reading comprehension to the tenth grade students of SMA Negeri 5 Lubuklinggau in the academic year of 2015/2016.